2019
DOI: 10.1002/jcp.28286
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Protection of miR‐19b in hypoxia/reoxygenation‐induced injury by targeting PTEN

Abstract: Objective To study the role and mechanism of microRNA 19b (miR‐19b) in hypoxia/reoxygenation (H/R)‐induced injury by targeting PTEN. Methods PC12 and BV2 cells induced by H/R were treated with miR‐19b mimics/inhibitors or small interfering PTEN (si‐PTEN), respectively. Lactate dehydrogenase (LDH) level, malondialdehyde (MDA), and superoxide dismutase (SOD) content was detected. Besides, cell viability and apoptosis were determined by 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide, Hoechst33342 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…The pharmacological inhibition of PTEN can further protect H9C2 cells from apoptosis in the context of hypoxia when used in combination with MSC-derived exosomes or miR-144 mimics. Other studies have also indicated that miRNAs can protect against hypoxiainduced cell apoptosis by inhibiting PTEN and targeting the AKT signaling pathway [39,40]. These findings further support the conclusion that MSC-derived exosomes exert anti-apoptotic effects on hypoxic CMCs by delivering miR-144 to cells where it targets the PTEN/ AKT pathway (Additional file 2: Figure S1).…”
Section: Discussionsupporting
confidence: 78%
“…The pharmacological inhibition of PTEN can further protect H9C2 cells from apoptosis in the context of hypoxia when used in combination with MSC-derived exosomes or miR-144 mimics. Other studies have also indicated that miRNAs can protect against hypoxiainduced cell apoptosis by inhibiting PTEN and targeting the AKT signaling pathway [39,40]. These findings further support the conclusion that MSC-derived exosomes exert anti-apoptotic effects on hypoxic CMCs by delivering miR-144 to cells where it targets the PTEN/ AKT pathway (Additional file 2: Figure S1).…”
Section: Discussionsupporting
confidence: 78%
“… 40 Restoring miR-19b reduces cell apoptosis and expedites the viability as well as increased Bcl-2/Bax ratios in H/R-induced PC12 and BV2 cells. 41 Except that, our study also indicated that inhibition of miR-19b in exosomes increased levels of IL-6 and decreased levels of IL-10. Li et al have supported that transfection of miR-19 inhibitor promotes release of cytokines IL-6 in fibroblast-like synoviocytes.…”
Section: Discussionsupporting
confidence: 52%
“…As it was reported previously, PTEN gene is one of the main negative regulators of PI3K/Akt pathway, and inhibition of PTEN can facilitate intrinsic regenerative outgrowth of adult peripheral axons [42]; from well-documented papers, we screened out several miRs that implicated with PTEN downregulation and neuronal repair. The literature on EVs suggested that miR candidates, such as miR-19b [43], miR-21 [40], miR-29b-3p [44], miR-233 [45], and miR-304-5p [46], would enable the activation of PI3K and downstream signaling molecules.…”
Section: Discussionmentioning
confidence: 99%